2012
DOI: 10.1080/09593330.2012.680917
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of organics in landfill leachate by immobilized white rot fungi,Trametes versicolorBCC 8725

Abstract: Immobilized Trametes versicolor BCC 8725 was evaluated for the biodegradation of the organic components of four different types of landfill leachate collected at different time periods and locations from the Nonthaburi landfill site of Thailand in batch treatment. The effects of carbon source, ammonia and organic loading on colour, biochemical oxygen demand (BOD) and chemical oxygen demand (COD) removal, and the reuse of immobilized fungi were investigated. It was found that fungi can remove 78% of colour, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the recent literature, different basidiomycota (e.g., Trametes versicolor , Dichomitus squalens , Trametes menziesii , Ganoderma australe ) have been investigated for landfill decolorization and detoxification with the involvement of oxidative enzymes [ 10 , 42 , 43 , 44 ]. The results are not always comparable since, sometimes, different parameters were monitored (COD and BOD instead of color and toxicity, phenolic content).…”
Section: Resultsmentioning
confidence: 99%
“…In the recent literature, different basidiomycota (e.g., Trametes versicolor , Dichomitus squalens , Trametes menziesii , Ganoderma australe ) have been investigated for landfill decolorization and detoxification with the involvement of oxidative enzymes [ 10 , 42 , 43 , 44 ]. The results are not always comparable since, sometimes, different parameters were monitored (COD and BOD instead of color and toxicity, phenolic content).…”
Section: Resultsmentioning
confidence: 99%
“…(Schiopu and Gravrilescu, 2010). Although some physical and chemical methods are effective in the removal of high strength pollutants, the high cost per volume unit is their major drawback (Bareither et al 2013; Saetang and Babel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The biological process showed that immobilized microorganisms system was effective for the removal of COD and nitrogen at 98.3 and 99.9 %, respectively. A study done by Saetang and Babel (2012) revealed that Trametes versicolor BCC 8725 could remove 78 color, 68 BOD 5 and 57 % COD from leachate sample within 15 days at optimum condition, respectively. They also claimed that organic loading and ammonia were the factors that affected the biodegradation.…”
Section: Bioreactormentioning
confidence: 99%